Untitled - Sustainability Council of Ventura County (Sustainability Council of Ventura County)
Addresses the pressing issues of economic and environmental stratification with the county as a whole. States that an "engagement" indicator needs to be devised to unlock links between environmental health and economic well-being. Without engagement, there is little possibility of "raising environmental consciousness.